2016
DOI: 10.1098/rsos.160539
|View full text |Cite
|
Sign up to set email alerts
|

A viscoelastic–stochastic model of the effects of cytoskeleton remodelling on cell adhesion

Abstract: Cells can adapt their mechanical properties through cytoskeleton remodelling in response to external stimuli when the cells adhere to the extracellular matrix (ECM). Many studies have investigated the effects of cell and ECM elasticity on cell adhesion. However, experiments determined that cells are viscoelastic and exhibiting stress relaxation, and the mechanism behind the effect of cellular viscoelasticity on the cell adhesion behaviour remains unclear. Therefore, we propose a theoretical model of a cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“…Cylindrical NPs and membrane surface tension are not considered. Kinetic reaction between receptor and ligand molecules [ 32 , 46 , 52 54 ], and viscoelastic deformation of cytoskeleton [ 23 , 55 ] are neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Cylindrical NPs and membrane surface tension are not considered. Kinetic reaction between receptor and ligand molecules [ 32 , 46 , 52 54 ], and viscoelastic deformation of cytoskeleton [ 23 , 55 ] are neglected.…”
Section: Discussionmentioning
confidence: 99%
“…In the cytoskeleton system, the filamentous actin (F-actin) (Figure 1) is one of the most major constituent building up many higher order structures in cells (e.g., stress fibers, lamellipodia, and filopodia) [8]. The arrangement and distribution of F-actin greatly dominates the mechanical properties of cells including viscoelasticity [9][10][11][12][13]. For example, the actin cortex is a thin layer that lies beneath the plasma membrane, maintaining and regulating cell topography [10].…”
Section: Introductionmentioning
confidence: 99%
“…The stress fibers are arranged in parallel by F-actin, connecting the cytoskeleton to the extracellular matrix via focal adhesions [12]. Wang et al reported that viscosity of F-actin can significantly increase stability of the cell adhesion [13]. The cellular protrusions including lamellipodium and filopodium located at the edge of cells is involved with the cell migration [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, two-pathway models of catch bond have been proposed to describe the kinetic reaction of catch-bond dissociation [11][12][13]. In addition to the chemical reactions of receptor-ligand bonds, the effect of other physical and mechanical factors, such as loading condition [14][15][16][17], deformation of substrate [18][19][20][21][22][23][24][25], membrane fluctuation [26][27][28][29], multiple bonds [30,31], cluster size [32], and cytoskeletal contraction [33,34] on cell or membrane adhesion have been discussed extensively. However, these studies focus on the occurrence of adhesion in a relatively quiescent environment.…”
Section: Introductionmentioning
confidence: 99%